(untitled) (Journal of Engineering, 2012)
Friction Stir Welding (FSW) is one of the most effective solid states joining process and has numerous potential applications in many industries. A FSW numerical tool, based on ANSYS F.E software, has been developed. The amount of the heat gone to the tool dictates the life of the tool and the capability of the tool to produce a good processed zone. Hence, understanding the heat transfer aspect of the friction stir welding is extremely important for improving the process. Many research works were carried out to simulate the friction stir welding using various softwares to determine the temperature distribution for a given set of welding conditions. The objective of this research is to develop a finite element simulation of friction stir welding of AA2024-W Aluminium alloy. Numerical simulations are developed for thermal conductivity, specific heat and density to know the relationship of these factors with peak temperature. Variation of temperature with input parameters is observed. The simulation model is tested with experimental results. The results of the simulation are in good agreement with that of experimental results.